Hiring, Churn, and the Business Cycle - Lazear, Edward P; Spletzer, James R (American Economic Review, 2012)
Hires occur for two reasons - to grow a business and to replace those who have left (churn). Churn is an important part of employment dynamics, allowing workers to move to their most productive use. We present evidence on churn from the Job Openings and Labor Turnover Survey (JOLTS). Churn is procyclical. During the 2007-09 recession, four-fifths of hiring reductions are associated with reduced churn, not with reductions in job creation. We estimate that the cost of reduced churn is about two-fifths of a percentage point of GDP annually throughout the three-and-one-half year period since the beginning of the recession.